Application of diversion of children in the action of criminal criminal justice in the children criminal justice system (Case study on Determination of Diversity Number 7 PenDiv 2019 PN Kln - Pambudi Tulus Nugroho; Suryawan Raharjo (Kajian Hasil Penelitian Hukum, 2020)
In order to deal with and overcome various problems of abuse committed by minors, it is necessary to consider the position of the child for the protection of children, namely non-discrimination in the child's best interests, survival and growth. The purpose of this study was to determine and analyze the application of diversion against children perpetrators of torture in the criminal justice system of children in the case of establishing diversion Number: 7  Pen.Div  2019 PN Kln, as well as to find out and analyze the obstacles experienced in applying the diversion against child perpetrators of criminal offenses in the juvenile justice system in the case of diversion Number: 7  Pen.Div 2019 PN Kln and how to overcome these obstacles. This research method is carried out using the statutory approach. Primary data and secondary data obtained are then analyzed by revealing the facts in sentence form. For all data obtained from the results of these studies the authors use qualitative analysis methods. Diversion is applied to child offenders of torture. Every criminal offense committed by a child can be resolved by restorative justice, as long as the child's case is in accordance with Article 7 of Law Number 11 Year 2012 concerning the Criminal Justice System for Children and the requirements for diversion are fulfilled, it must be pursued restorative justice. Obstacles experienced in the application of diversion against child offenders, including lack of community understanding, lack of deterrent effect, short investigation time, victims and suspects there are still blood relations, children are less cooperative, lack of parental awareness, lack of cooperation with Social Workers, difficult children found, parents who are passive as well as family support for children are absent and the education and community sides do not support.